Saliva Sensors - Aroutiounian, V. M.
Saliva, an alternative body fluid that is easily accessible and contains trace amount of glucose can be potentially used for the noninvasive monitoring of diabetes. A positive correlation between blood glucose (BG) and stimulated salivary glucose (SG) in diabetics has been reported. The main goal of Self-Monitoring of Blood Glucose is to monitor a person's blood glucose at different time intervals which can aid a doctor in adjusting medication/insulin dose and is also useful to a patient in evaluating his/her response to therapy. Versions of saliva glucose (SG) sensor fabrication are reported. SG analysis with reference method was discussed. Salivary protein biomarkers are reported. Special strips or chips and saliva tests are presented.
Keywords: Physics